PENGARUH LITERASI KEUANGAN, PENGETAHUAN INVESTASI, MOTIVASI INVESTASI DAN FAKTOR DEMOGRAFI TERHADAP MINAT INVESTASI (PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS DI PERGURUAN TINGGI KOTA BENGKULU) - Yusmaniarti, Yusmaniarti; Viona, Dea (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to analyze the influence of financial literacy, investment knowledge, investment motivation, and demographic factors on the investment interest of students in the Faculty of Economics and Business at a university in Bengkulu City. The research method used a quantitative approach with data collection through questionnaires. The study population included students from four universities in Bengkulu City: the University of Bengkulu, Muhammadiyah University of Bengkulu, Dehasen University of Bengkulu, and Hazairin University of Bengkulu. Data analysis was performed using multiple linear regression with the assistance of SPSS version 25. The results indicate that financial literacy, investment knowledge, investment motivation, and demographic factors partially have a positive and significant effect on students' investment interest. Simultaneously, these four independent variables also significantly influence students' investment interest. The coefficient of determination (R²) of 0.391 indicates that financial literacy, investment knowledge, investment motivation, and demographic factors explain 39.1% of the variation in students' investment interest, with the remainder influenced by factors outside the study. These findings emphasize the importance of improving financial literacy, investment understanding, and motivating students to foster investment interest from an early age. Keywords: Financial Literacy, Investment Knowledge, Investment Motivation, Demographic Factors, Investment Interest